Effects of disease resistance and fungicide treatments on scald and yield in four barley cultivars - Cromey, M.G.; Butler, R.C.; Munro, C.A.; Ebdon, S.E. (New Zealand Plant Protection, 2000)
New Zealand barley cultivars differ in resistance to leaf scald caused by Rhynchosporium secalis Four cultivars (one highly resistant two moderately resistant and one susceptible) were selected for evaluation in a field trial under differing fungicide regimes Fungicide applications were used to encourage no epidemic (early late fungicide applications) an early epidemic (late applications only) a late epidemic (early applications only) or a full epidemic (no applications) Disease severity was assessed six times The resistant cultivar Dash was virtually free of scald at all assessment dates Disease progressed rapidly in untreated plots of the susceptible cultivar Optic from the first appearance of scald (13 August) until all leaves were fully diseased (midNovember) Fungicide applications reduced scald severity in Optic but did not eliminate the disease The two moderately resistant cultivars had intermediate disease levels Yields reflected relative disease severity with the greatest yield differences between full and no disease control being recorded in Optic Control of the late epidemic increased yield to a much greater extent than the early epidemic